2019
DOI: 10.1111/ajt.15565
|View full text |Cite
|
Sign up to set email alerts
|

Prescription opioid use before and after heart transplant: Associations with posttransplant outcomes

Abstract: Impacts of the prescription opioid epidemic have not yet been examined in the context of heart transplantation. We examined a novel database in which national U.S.transplant registry records were linked to a large pharmaceutical claims warehouse (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) to characterize prescription opioid use before and after heart transplant, and associations (adjusted hazard ratio, 95% LCL aHR 95% UCL ) with death and graft loss.Among 13 958 eligible patients, 40% filled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 27 publications
(69 reference statements)
0
27
0
Order By: Relevance
“…Pre‐ and post‐transplant opioid use was associated with a graded increased risk of death and all‐cause graft failure after kidney transplantation 8,10 . Similar risk relationships were recently documented among liver and heart transplant recipients 9,11 . Opioid use before living donor nephrectomy was also associated with increased risk of readmission after donation surgery 12 …”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Pre‐ and post‐transplant opioid use was associated with a graded increased risk of death and all‐cause graft failure after kidney transplantation 8,10 . Similar risk relationships were recently documented among liver and heart transplant recipients 9,11 . Opioid use before living donor nephrectomy was also associated with increased risk of readmission after donation surgery 12 …”
Section: Introductionmentioning
confidence: 64%
“…Distributions of clinical and demographic characteristics among recipients with each class of pretransplant benzodiazepine use, compared with no benzodiazepine use, were compared by chi‐square test. Propensity models for the likelihood of benzodiazepine use in the pretransplant period were constructed by multivariable logistic regression, and regression models were adjusted by stratification for quintile of propensity score, as per previous methods 7‐11,15 . Adjusted associations of pretransplant benzodiazepine use with post‐transplant death and all‐cause graft failure (adjusted hazard ratio with 95% upper and lower confidence limits, LCL aHR UCL ) were quantified by multivariate Cox regression including adjustment for recipient, donor, and transplant clinical factors.…”
Section: Methodsmentioning
confidence: 99%
“…TCs are commonly prescribed opioid pain medications, which may come with certain risks. Opioid prescription rates the year before SOT are 43.1% among KTCs (Lentine et al, 2018) and 40% among HTCs (Lentine et al, 2019); high levels of posttransplant opioid use have been associated with increased risk of death and/or graft loss (Lentine et al, 2019). Higher morphine equivalent levels pretransplant are found to result in the highest risk of death and graft loss after SOT (Lentine et al, 2019;Randall et al, 2017).…”
Section: Prescribed Opioidsmentioning
confidence: 99%
“…Opioid prescription rates the year before SOT are 43.1% among KTCs (Lentine et al, 2018) and 40% among HTCs (Lentine et al, 2019); high levels of posttransplant opioid use have been associated with increased risk of death and/or graft loss (Lentine et al, 2019). Higher morphine equivalent levels pretransplant are found to result in the highest risk of death and graft loss after SOT (Lentine et al, 2019;Randall et al, 2017). Distinguishing between opioid use and misuse requires a review of prescription records and early refills, a review of state databases of controlled substances and drug screen reports, and patient, provider, and caregiver input.…”
Section: Prescribed Opioidsmentioning
confidence: 99%
“…Opiates have an addiction potential and have been linked to reduced cognition, decreased medication adherence, and increased risk of death [71,72]. Importantly, a large multi-center study reported that prescription opiates were associated with an increased mortality risk following cardiac transplantation [73]. In contrast, cannabis has a lower potential risk for overdose, less addiction potential, and fewer associated deaths [74,75].…”
Section: Similarities Between Prescription Opiates and Prescription (Medical) Cannabismentioning
confidence: 99%